2019
DOI: 10.1111/nyas.14141
|View full text |Cite
|
Sign up to set email alerts
|

Metformin promotes mitophagy in mononuclear cells: a potential in vitro model for unraveling metformin's mechanism of action

Abstract: Increased oxidative stress in patients with type 2 diabetes mellitus (T2DM) results in abnormalities in cell repair processes, such as mitophagy, which compromises mitochondrial function and contributes to insulin resistance and β cell failure. Metformin, widely recommended in the management of T2DM, exerts its pleiotropic effects via 5ʹ‐AMP–activated protein kinase (AMPK); however, its effect on mitophagy remains elusive. Recent evidence demonstrates that peripheral blood mononuclear cells (PBMCs) express ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…These findings suggest that metformin significantly influenced the process of mitophagy de novo, and this propitious effect was observed to be independent of its efficacy on glycaemic control, in contrast to voglibose. In line with our findings, our previous in vitro study revealed that there was an increased formation of mitophagosomes as well as enhanced mitophagic flux in mononuclear cells following metformin exposure …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings suggest that metformin significantly influenced the process of mitophagy de novo, and this propitious effect was observed to be independent of its efficacy on glycaemic control, in contrast to voglibose. In line with our findings, our previous in vitro study revealed that there was an increased formation of mitophagosomes as well as enhanced mitophagic flux in mononuclear cells following metformin exposure …”
Section: Discussionsupporting
confidence: 93%
“…Our findings highlight that metformin caused a significant increase in p‐AMPKα (T172) levels, whereas voglibose did not display any effect on the same. Therefore, it is conceivable that metformin regulates mitophagy, which is mediated via the activation of the AMPK as also supported by our previous in vitro observations …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Autophagy has different stages that are regulated directly by AMPK, where in its early stages it acts by activating Beclin-1 [85] and in parallel inactivating mTOR and phos-phorylating ULK1, a key autophagic initiator [82,85,97], and in the final stages stimulating the conversion from LC3-I to LC3-II [85]. The early stages of autophagy have been related to an enhancement of osteogenic differentiation of PDL stem cells, however in late stages this mechanism seems to be reduced, which may indicate a suppression of autophagic activity [85].…”
Section: Cellular Debris Eliminationmentioning
confidence: 99%
“…Metformin is a widely used antidiabetic drug that has been shown to extend lifespan in animal models of aging, and to increase human healthspan (251 -253). Metformin was also reported to activate mitophagy (254). It is known that metformin directly inhibits NADH dehydrogenase, and it was shown that this inhibition leads to inhibition of mPTP and protection from I/R damage (255 -257).…”
Section: Lifespan and Healthspan Extension Paradigms And Mptpmentioning
confidence: 99%